Accessibility in the Metaverse: A Rapid Review of the Literature - Fernandes, Filipe; Ferreira, Priscyla; Werner, Cláudia (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
The Metaverse gained popularity with the rebranding of Meta, and since then, headsets, multimodal devices, and applications with immersive experiences have evolved and been applied in various domains such as marketing, education, and industry, among others. However, we question whether individuals with disabilities are also able to have immersive experiences. Therefore, this study aims to conduct a Rapid Reviewto identify the state of the art in accessibility within the Metaverse. From 145 studies identified in the Scopus search engine, 141 studies were excluded, resulting in 4 articles for data extraction. We found that there is significant ambiguity in the use of the term "accessibility," which led to a high exclusion rate of studies. Furthermore, we did not identify any work that implements assistive technologies to enable immersive experiences for individuals with disabilities. For future research, we aim to conduct a more comprehensive systematic review to obtain more consistent results on the state of the art in accessibility within the Metaverse.